Pengaruh ekstrak propolis dalam meningkatkan fibroblas untuk remodeling di daerah tarikan pada pergerakan gigi Ortodonti - Budi Handayani; Lisdiana Mardanus (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: Orthodontic treatment requires time so, duration of orthodontic treatment time needs to be shortened in various ways. Flavonoid is an active content of propolis, that might accelerate tissue regeneration. Flavonoid might increase the number of fibroblast at tension side of orthodontic tooth movement. Purpose: The purpose of this study was to examine the effect of propolis extract gel towards the number of fibroblasts at tension side to accelerate orthodontic tooth movement. Materials and Methods: Thirty male Cavia cobayas weredivided into three groups. The first group, ( P) was given treatment to make orthodontic tooth movement and propolis extract gel. The second group, K(+) was given treatment and NaCMC gel. The third group, K(-) was served as control. After 14 days, the Cavia cobayas weresacrified. Fibroblast number was examined with light microscope 400 X. Result: Mean and SD in K(-):100 ± 13,2; K(+):80 ± 13,05; (P):176 ± 17,9. The result of ANOVA test showed significant increase in the number of fibroblasts. The LSD test showed significant result in all groups with significance result p ≤ 0,05. Conclusion: Propolis extract can increase fibroblast number to accelerate orthodontic tooth movement.